Screening for Theileria parva secretory gene products by functional analysis in Saccharomyces cerevisiae - Musembi, S.; Janoo, R.T.K.; Sohanpal, B.K.; Ochanda, H.; Ole-MoiYoi, O.K.; Bishop, Richard P.; Nene, Vishvanath M. (Elsevier, 2000)
Molecules located on cell surfaces and those that are secreted from the cell frequently play a critical role in cell biology by mediating interaction with the external environment. These types of parasite molecules often constitute targets for protective host immune responses and are thus of additional interest as candidate vaccine antigens. Targeting of proteins to an extra-cellular environment usually involves trafficking through components of the secretory pathway. Most proteins access this pathway via insertion into or translocation across the endoplasmic reticulum, a process dependent on a signal sequence at or close to the N-terminus that exhibits conserved features across a wide range of eukaryotic organisms, although the signals are degenerate in amino acid sequence (1-3). The secretory signal sequences of proteins from different organisms are functionally interchangeable, highlighting the conserved nature of the secretory apparatus (4). These observations led to the development of a 'signal sequence trap' (SST) methodology to identify secretory molecules by expression screens in a heterologous system (5). Export of a few eukaryotic proteins occurs by a different mechanism (1) and these exceptions to the general rule would not be expected to function in the SST system. The original SST method used a COS cell expression cloning system and depends on complementation of a deleted signal sequence on a gene encoding the chain of human interleukin-2 receptor (5). This system is dependent on successive rounds of enrichment of plasmid recovered from transfected cells and has been used to identify many novel higher eukaryotic secretory proteins (5,6) including secreted proteins from the salivary glands of Anopheles gambiae (7). A simplified SST method has been described that exploits the requirement of a secreted enzyme in permitting growth of Saccharomyces cerevisiae when sucrose is the sole carbon source (8,9). The yeast SST system has identified previously characterised human proteins containing a cleaved or non-cleaved secretory signal sequence and proteins that are targeted to intracellular organelles (9), indicating flexibility of the method and predicting identification of a wide repertoire of secretory proteins. It has also been used to identify secretory proteins of Drosophila (10) and Arabidopsis (11). In this report we examine the suitability of one of two yeast SSt system (8,9) for the identification of secretory proteins from Theileria parva, an intracellular protozoan pathogen that usually causes a lethal disease in cattle known as East Coast fever (ECF) (12).